Towards quality service delivery outcomes: what can local governments’ own-source revenue do? - Dick-Sagoe, C. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
Local governments are mandated, through decentralisation, to mobilise own-source revenues and channel them into poverty reducing service provision like education and health. Arguably, the best way to measure the benefits from poverty reducing public service provision is through quality service outcomes (such as quality education outcomes). This paper argues that the structure of local government finances, where local governments depend heavy on intergovernmental transfers is not a problem to consider much on when it comes to improved local service delivery. However, much focus should be geared towards the performance in the mobilisation of own-source revenue and its relationship with poverty reducing public service provision outcomes at the local level. The reason is that decentralisation is a medium to enhance the participation of the local people. The best way to enhance this local participation is through increased accountability from the local governments to the local people. Local participation attracts local innovations which are necessary for improved public service outcomes. Existing studies show that the collection of own-source revenues enhances local accountability, which is prerequisite for achieving quality public service delivery outcomes. This paper argues that increases in own-source revenues will impact more on poverty reducing public service provision outcomes. Longitudinal panel data of revenue and service delivery outcome reports for the 20 local governments in the Central Region of Ghana, from 2011 to 2015, were used to answer the research question for the study. The research question is ‛‛does increases in own-source revenues improve quality of public service delivery outcomes at the local level?’’ The study found no statistical relationship between service delivery outcomes (core textbook provision per child) and own-source revenues. On the other hand, there was a moderate statistical relationship between own-source revenues and pupil per trained teacher ratios at 0.01 alpha value. Recommendations were made for local governments to increase own-source revenue mobilisation efforts as it impacts positively on efforts to improve local public service delivery outcomes, especially if the focus is on improving pupil per teacher ratio at the local level.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Local government; Service delivery; Quality service outcomes; Own-source revenue; New public management; Municipal services -- Finance; Municipal revenue; Local government; Local finance